Prosody in syntactic encoding - Kentner, Gerrit; Kremers, Joost (Linguistische Arbeiten (Max Niemeyer Verlag) ;, 2020)
What is the role of prosody in the generation of sentence structure?A standard notion holds that prosody results from mapping a hierarchical syntactic structure onto a linear sequence of words. A radically different view conceives of certain intonational features as integral components of the syntactic structure. Yet another conception maintains that prosody and syntax are parallel systems that mutually constrain each other to yield surface sentential form.The different viewpoints reflect the various functions prosody may have: On the one hand, prosody is a signal to syntax, marking e.g. constituent boundaries. On the other hand, prosodic or intonational features convey meaning; the concept "intonational morpheme" (as e.g. an exponent of information structural notions like topic or focus) puts prosody and intonation squarely into the syntactic representation. The proposals collected in this book tackle the intricate relationship of syntax and prosody in the encoding of sentences. The contributions build their cases on the basis of solid empirical evidence, adducing data from experiments or from the careful analysis of natural speech. The volume thus represents a state of the art survey of research on the syntax-phonology interface.